The relationship between somatic cells and the concentration of lactose is associated with mastitis in dairy cows (Journal of Hama University, 2022)
The study aims to determine the relationship between an account of somatic cells (SCC) in milk and concentration of lactose as indicator to occur mastitis in dairy herds 160 milk samples were collected form 40 milk .dairy cows form start of lactation period up to dairy period (1/9/2020  to 1/9/2021).Results reported that the arithmetic mean of somatic cells in milk samples for tested cattle were 162x103 ∓ 17.72 arithmetic means between cattle in the first lactation were varied between 154x103 ∓ 15.84 and 157.7x103 ∓ 18.83 in second lactation, while reported 164.6x103 ∓ 13.45 in third lactation , and 171x103 ∓ 17.07 in the forth lactation. The total lactose concentration in milk samples of tested cows was %4.50 ∓ 0.045 arithmetic means of total lactose among cattle samples in first lactation %40.52 ∓ 0.47 cattle samples in second lactation%4.51 ∓ 0.044, while it was in the third lactation %4.49 ∓ 0.038 and %4.48 ∓ 0.04 in the forth lactation . Results showed an increase in lactose value consequently with increase somatic cell account that refer to presenting in inflammatory indicator in gland udder. As long as there the severity of inflammation increased reported decrease in lactose value as a percentage value. The normal parameter reporting in study samples was %4.52, it was pursue to  decrease with rise value of somatic cell, it was started from value of 51x103 somatic cell/ml milk up to reached to decrease value of lactose as %40.
Keywords: Mastitis - somatic cells-Lactose- Dairy cattle